Fatores de risco para o câncer do esôfago no Estado de Goiás - MOTA, Orlando Milhomem da (2012)
Context and Objectives: This thesis was divided into two parts. In the first one risk factors for esophageal cancer were analyzed using data from a case and control study. In the second part the survival of the esophageal cancer patients from the first study was analyzed. The aim of this study was to evaluate the risk factors for esophageal cancer in an area where the incidence is low and survival of patients undergoing treatment in a low-volume hospital. Methods: This is a case-control study hospital based. The analysed variables were: sociodemographic data, habits, (tobacco and alcohol). The sample was analyzed using the chi-square test, Mann-Whitney test and Mantel-Haenszel approach for multivariate analysis. The strength of the risk was calculated using odds ratios (OR) with significance defined at 5% and 95% confidence intervals. Results: It was analysed 99 cases of esophageal cancer and 223 controls. The risk of esophageal cancer was higher in patients ≥ 55 years (OR = 1.95; P= 0.01). Patients from rural areas had almost five times high risk in comparison with urban. (OR 4.9; P < 0.001). Smoking was a risk factor among cases (OR = 3.8; P < 0.001), exposure to smoke from wood stoves (OR = 4.42; P < 0.001) as well as frequent consumption of apples and pears OR 0,27 (CI95% 0,11 -0,70) and fish OR 0,23 (CI 0,07 0,75), were found as protective factors. We analysed the survival of 99 cases of the esophageal cancer. The average survival was 32.7% for the first year, 25,2% for the second year and 11,0% for the third year. Conclusion: In a region in which the incidence of esophageal cancer is low, the most significant risk factors were living rurally, smoking, exposure to a wood stove and dary products consumption. Survival in patients with esophageal cancer for the third year was 11%, the patients undergoing surgical treatment survival in the third were 19,6%.